Influence of precession electron diffraction parameters and energy filtering on reduced density function analysis of thin amorphous silica films—implications for structural studies - Chou, Y-J; Borisenko, KB; Das, PP; Nicolopoulos, S; Gemmi, M; Kirkland, AI (MDPI, 2023)
We investigated the influence of precession angle, energy filtering and sample thickness on the structural parameters of amorphous SiO2 thin films from the electron reduced density functions obtained by applying precession electron diffraction. The results demonstrate that the peak positions in the electron reduced density functions are generally insensitive to the studied experimental conditions, while both precession angle and energy filtering influence peak heights considerably. It is also shown that introducing precession with small angles of up to 2 degrees and energy filtering results in higher coordination numbers that are closer to the expected theoretical values of 4 and 2 for Si and O, respectively, for data obtained from a thicker sample.